(untitled) (REMUNOM, 2023)
Enterobacter cloacae, a bacterium found in the gut microbiota of healthy individuals, may represent an important opportunistic microorganism causing hospital-acquired infections, such as nosocomial pneumonia in patients admitted to Intensive Care Units (ICUs). This bacterium has shown resistance to several antimicrobials available on the market. Therefore, it is worth emphasizing the growing search for natural products, among them essential oils, because they are products of plant origin, low cost and easy access by the population. Among the essential oils that present antimicrobial, antifungal and anti-adherent activity is Origanum vulgare. Thus, the objective of this research was to analyze the antibacterial and anti-adherent activity of Origanum vulgare essential oil against Enterobacter cloacae. Methodological tests were carried out using the broth microdilution techniques in 96-hole plates to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC), and the inclined tube technique to determine the Minimum Inhibitory Concentration of Adherence (MIC), in the presence of 5% sucrose. Thus, it was found that the essential oil of Origanum vulgare presented an MIC of 128 µg/mL and MBC of 256 µg/mL against Enterobacter cloacae. On the other hand, the MIC of the essential oil and the positive control (Chlorhexidine Digluconate 0.12%) was not found at the concentrations experimented. Thus, it was possible to conclude that the essential oil of Origanum vulgare presented high antimicrobial potential and was considered bactericidal, although there was no anti-adherent activity against the ECL 41 strain, at the concentrations tested and in the methodology applied.